The The Correlation Of Human Resource Management To The Quality Of Teachers In Learning : Indonesia - Atika Nur Hidayati; Tomi Kurniawan (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2021)
This study aims to determine the effect of human resource management on the teaching quality of educators at MIN 6 Lampung Selatan. This type of research is a correlation. Collecting data in this study used a human resource management scale and a scale of quality educators. The prerequisite test for data analysis included normality and linearity tests. Data analysis was performed using correlation calculations, with linearity test, homogeneity test, F test, and regression test assisted by the Statistical Package for Science (SPSS 25). The results of this study indicate that human resources have a significant effect on the teaching quality of teachers in MIN 6 Lampung Selatan.